Lipid Formation and mRNA Expression of Key Adipogenic Genes in the Liver of Athens Canadian Random Breed and COBB Chicken Breeds During the Embryogenic Period - Kim, Haein; Sedlacek, P.D.; Kim , W.K. (International Journal of Poultry Science, 2017)
Objective: This study was designed in order to compare the lipid formation and the expression of key lipid metabolism genes in the livers between 2 types of chicken breeds during embryonic development. Methodology: A total of 36 fertilized eggs from Athens Canadian Random Breed (ACRB: Unselected chicken), breeder hens and commercial breeder hens (COBB: Selected for rapid growth) were incubated at 37.5°C and 60% relative humidity. Liver samples were collected at embryonic day (E)14 and 18. The mRNA expression of key adipogenic genes, such as adipocyte protein 2 (AP2) and peroxisome proliferator-activated receptor gamma (PPAR-ɣ), was detected using quantitative real time polymerase chain reaction (qRT-PCR). Lipid droplet accumulation was also analyzed and compared using a histological method between COBB and ACRB on E14 and E18. Results: In this study, the histological analyses of COBB and ACRB livers showed no significant difference in the amount of lipid droplets accumulated. The mRNA expression of AP2 and PPAR-ɣ also was not significantly different between COBB and ACRB on E14 and E18. Conclusion: The results indicate that lipid formation in the liver during embryonic development is not affected by any genetic selection, suggesting that lipid metabolism changes between two chicken breeds could be initiated after hatch.